PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN HABITS OF STRIVING FOR ACCURACY AND PRECISION (HSAP) MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) BERBASIS GAYA KOGNITIF SISWAKELAS VII : Kuasi Eksperimen pada Siswa SMPN 5 Bandung - Salwah, - (2014)
Penelitianinibertujuanuntukmengetahuiperbedaankemampuandanpeningkatankemampuanberpikirkritismatematisantarasiswa yang mendapatpembelajarandenganpendekatan RME berbasisgayakognitifdansiswa yang mendapatpembelajarandenganpendekatankonvensional. Penelitianiniadalahpenelitiankuasieksperimendengandesainkelompokkontrol non-ekuivalen.Populasidaripenelitianiniadalahsemuasiswakelas VII padasalahsatu SMPN di kota Bandung, pada semester genaptahunajaran 2013/2014. Dipilihduakelassecarapurposivesebagaisampelpenelitianyaitukelas VII-E sebanyak 28 siswasebagaikelaskontroldankelas VII-H sebanyak 27 siswasebagaikelaseksperimenTeknikpengumpulan data padapenelitianiniyaitu: (1) memberikanpretesdanpostesberupateskemampuan BKM, (2) melakukanobservasi yang berkaitandengan HSAP siswadanobservasiaktivitas guru, (3) memberikanangket yang berkaitandengan HSAP siswa. Analisis data dilakukandenganmenggunakanuji-t.berdasarkanhasilpenelitiandiperolehbahwa: (1) terdapatperbedaankemampuan BKM antarasiswa yang mendapatpembelajarandenganpendekatan RME berbasisgayakognitifdansiswa yang mendapatpembelajarandenganpendekatankonvensional, (2) peningkatankemampuanberpikirkritismatematisdankualitaspeningkatankemampuanberpikirkritismatematissiswa yang mendapatkanpembelajaranmelaluipendekatan RME berbasisgayakognitiflebihbaikdaripadasiswa yang mendapatkanpembelajaranmelaluipendekatankonvensional, (3) kemampuanberpikirkritismatematissiswa yang memilikigayakognitiffield independent (FI) lebihbaikdaripadasiswa yang memilikigayakognitiffield dependent (FD), (4) siswa yang mendapatkanpembelajarandenganpendekatan RME berbasisgayakognitifmemilikikebiasaanberjuang demi ketelitiandanketepatan yang beradapadakategoripelajaryaitusiswaakanmemeriksakembalipekerjaannyabiladisuruholeh guru. The aims of this study are to determine the difference of MCT ability and the enhancement of students' MCT ability between students who obtained learning through RME approach based on cognitive style and students who obtained conventional approach. This study is a quasi-experimental research with non-equivalent control group design. The population of this study is all students of grade VII in one of junior high school in Bandung, in the second semester of academic year 2013/2014. Two classes are selected purposively as sample of study, that is: year VII-E as many as 28 students are selected as control group and year VII-H as many as 27 students as experimental group. Techniques of data collection in this study consist of: (1)give pretest and posttest to students in the form of test MCT ability, (2) observe related to the students' HSAP and teacher's activities, (3) give the questionnaire related to the students' HSAP. Data analysis is conducted by using t-test.The result of this research showed that:(1) there is the difference of MCT ability between the students are taught by RME approach based on cognitive style and students are taught by the conventional approach. (2) the enhancement of students' MCT ability and the enhancement quality of students' MCT ability who obtained learning through RME approach based on cognitive style better than students who obtained learning through conventional approach. The enhancement quality of students' MCT ability are in the middle category, both of the class are taught by RME approach based on cognitive style and the class are taught by conventional approach, (3) MCT ability of students who had field independent (FI) cognitive style better than MCT ability of students who had field dependent (FD) cognitive style, (4) students who obtained learning through RME approach based on cognitive style has HSAP in the "learner" category, that category is the student will review their work when told by the teacher.